Immunological analysis of active site loop of lactate dehydrogenase from two Plasmodium species - Celik, V.; Sadak, D.; Turgut-Balik, D. (Blackwell Publishing, 2006)
[Abstract Not Available]
31st Congress of the Federation-of-European-Biochemical-Societies (FEBS) -- JUN 24-29, 2006 -- Istanbul, TURKEY